2002
DOI: 10.1002/jemt.10040
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular distribution of metals in molluscs

Abstract: The cellular processes involved in metal metabolism in molluscs are reviewed, with emphasis on the contribution of microscopy (AMG, ARG, EPMA, and SIMS) to both basic research of metal cell biology and applied environmental research. In molluscs, metal uptake may occur by facilitated diffusion, active transport, or endocytosis, and can be enhanced by MT synthesis or formation of mineralized granules. In aquatic molluscs, gills constitute a key interface for dissolved metal uptake, where metals are bound to MT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
206
1
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(230 citation statements)
references
References 181 publications
(386 reference statements)
12
206
1
11
Order By: Relevance
“…1). The irregularity of epithelium and loss of interlamellar tissue of the gill filaments may have significant effects on respiration and , isoleucine; 2, alanine; 3, succinate; 4, betaine; 5, arginine; 6, glycine; 7, tyrosine; 8, phenylalanine; and 9, aspartate. food uptake, as previously reported (Marigómez et al, 2002;Au, 2004;Abdel-Nabi et al, 2007), although food clearance rates were not measured in the current study. In support of this, a previous study showed that repeated exposure to hypoxia reduces the clearance rate (Kozuki et al, 2013).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…1). The irregularity of epithelium and loss of interlamellar tissue of the gill filaments may have significant effects on respiration and , isoleucine; 2, alanine; 3, succinate; 4, betaine; 5, arginine; 6, glycine; 7, tyrosine; 8, phenylalanine; and 9, aspartate. food uptake, as previously reported (Marigómez et al, 2002;Au, 2004;Abdel-Nabi et al, 2007), although food clearance rates were not measured in the current study. In support of this, a previous study showed that repeated exposure to hypoxia reduces the clearance rate (Kozuki et al, 2013).…”
Section: Discussionsupporting
confidence: 68%
“…The gills and hepatopancreas of bivalve species are responsive and sensitive to environmental stressors (Marigómez et al, 2002;Au, 2004;Abdel-Nabi et al, 2007). In the present study, we observed that the gills of R. philippinarum exposed to hypoxia lost their structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These are often used as indicators of freshwater metal pollution, because they tend to rapidly accumulate metals and radionuclides (uranium) exposure pathways. As prey for trophic exposure experiments, we selected the Asiatic clam, C. fluminea, which is well known for its high capacity for metal bioaccumulation [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…With this, essential metals in excess of metabolic requirements and non-essential metals are detoxified and/or excreted (Rainbow, 2002;Campbell et al, 2005Campbell et al, , 2008. Excess of metals can be bound to the metal binding protein metallothionein (Vijver et al, 2004;Van Campenhout et al, 2008) and (subsequently) immobilized within granules (Marigómez et al, 2002). Metal-rich granules can be excreted via faeces or basal exocytosis towards haemocytes (Desouky, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Techniques like differential centrifugation (Wallace et al, 2003), chromatographic separation (Van Campenhout et al, 2008), and microscopic analysis (Marigómez et al, 2002) give the opportunity to study the internal distribution of the metals. However, it is not yet fully understood whether and how factors such as total tissue concentration, uptake rate and physiological condition are involved in the capacity of metal detoxification.…”
Section: Introductionmentioning
confidence: 99%